If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(m-2)=2(5m-4)
We move all terms to the left:
8(m-2)-(2(5m-4))=0
We multiply parentheses
8m-(2(5m-4))-16=0
We calculate terms in parentheses: -(2(5m-4)), so:We get rid of parentheses
2(5m-4)
We multiply parentheses
10m-8
Back to the equation:
-(10m-8)
8m-10m+8-16=0
We add all the numbers together, and all the variables
-2m-8=0
We move all terms containing m to the left, all other terms to the right
-2m=8
m=8/-2
m=-4
| 5(y+8)+2y=26 | | 5(8+v)-8v=-2+3v | | 6-t=-5+6 | | 6a+2=20+3a | | 2x+26+x+32=180 | | 2x/8=10/12 | | 3x+19=7x+5=2x+8 | | 11=-2n-5 | | 16=4y+4 | | 4x+3.75=63.75 | | xx10=69 | | (7x+3)(2x-3)=180 | | -3=2p+3 | | 5(-6b-6)-8b=34-6b | | .2x+29-0.8=5 | | 15(2x+3)=10-5x | | o-1/6=1/2 | | 5+3b;3b=+5 | | 21=13-2x | | -7(1-n)-2=7(n+4)+2 | | 7c=8c+5 | | D=d-8 | | |2x+4|=|3x-1| | | 7x-27=3x-29=180 | | -11=5(x-7)-8x | | .25x-4=8 | | -7=p/3 | | 4−5x+10=18-4x | | -9-2n=7 | | 0.4(8x+40)=3.2(x+5) | | 6(2x-4)-2x=36 | | 5(x-6)=18+2x |